The characteristics of neonatal sepsis in Low Birth Weight (LBW) infants at Sanglah General Hospital, Bali, Indonesia in 2018 - Ni Luh Gede Wahyuni Suismaya; I Wayan Dharma Artana (Intisari Sains Medis, 2020)
Background: Sepsis is one of the most common causes of mortality and long terms morbidity among infants. It is known to be related to Low Birth Weight (LBW) due to the lack of immunity function to resist the infection. This study aims to identify the characteristics of neonatal sepsis in LBW infants in Sanglah General Hospital.Method: A retrospective cross-sectional study was conducted in the Neonatal Care Unit, Sanglah General Hospital, during January-December 2018 period among 135 neonates. Samples were taken using total sampling for neonates who had LBW and diagnosed with sepsis. Uncompleted data and voluntarily discharge patients were excluded from the study. Data regarding baseline characteristics of respondents, major and minor risk factors, laboratory results of sepsis, as well as blood culture, were analyzed using SPSS version 23 for Windows.Result: Most of respondents were male (54.1%), followed by bodyweight 1,500-2,499 grams (58.5%), and preterm labor (<32 weeks) (86.7%). The average length of stay was 21.30Â±19.28 days. The vast majority of infants diagnosed as Early Onset Sepsis (EONS) (89.6%). Most of the patients had normal leukocyte count (93.3%), neutrophilia (95.6%), low I/T ratio (70.4%), normal platelets (67.4%), and high procalcitonin (98.5%). The blood culture showed the most microorganism was Enterococcus faecalis (6.00%) in gram-positive bacteria.Conclusion: This study found that most of the respondents were male, followed by preterm labor, EONS, normal leukocyte count, low I/T ratio, high procalcitonin, as well as Enterococcus faecalis as the most common gram-positive bacteria.Â